The potential role and rationale for treatment of heart failure with sodium-glucose co-transporter 2 inhibitors - Butler, Javed; Brückmann, Martina (European journal of heart failure, 2017)
Heart failure (HF) and type 2 diabetes mellitus (T2DM) are both growing public health concerns contributing to major medical and economic burdens to society. T2DM increases the risk of HF, frequently occurs concomitantly with HF, and worsens the prognosis of HF. Several anti-hyperglycaemic medications have been associated with a concern for worse HF outcomes. More recently, the results of the EMPA-REG OUTCOME trial showed that the sodium-glucose co-transporter 2 (SGLT2) inhibitor empagliflozin was associated with a pronounced and precocious 38% reduction in cardiovascular mortality in subjects with T2DM and established cardiovascular disease [Correction added on 8 September 2017, after first online publication: “32%” in the previous sentence was corrected to “38%”]. These benefits were more related to a reduction in incident HF events rather than to ischaemic vascular endpoints. Several mechanisms have been put forward to explain these benefits, which also raise the possibility of using these drugs as therapies not only in the prevention of HF, but also for the treatment of patients with established HF regardless of the presence or absence of diabetes. Several large trials are currently exploring this postulate.